Noise Analysis in 5G Network Transmission Systems - ⁠Alan Abdus Somad; ⁠Bayu Nugroho; Varissa Nisrina Yakin; Rustamaji (Journal of Engineering Science and Technology Management, 2026)
The advancement of 5G networks offers high-speed communication, low latency, and massive connectivity, but faces challenges from noise and interference in the sub-6 GHz and mmWave bands (Rappaport et al., 2019). This study aims to analyze the characteristics and dominance of noise in 5G transmission systems and evaluate efficient mitigation strategies such as adaptive beamforming. Using a qualitative approach to secondary data analysis, the population includes publications on 5G noise from 2016 to 2025 from Google Scholar, with a purposive sample of 20-25 primary sources including 3GPP standards. The instruments are scientific articles and technical reports; analysis techniques include thematic clustering, comparative interpretation, and source triangulation (Sugiyono, 2021). The results show that thermal noise dominates sub-6 GHz due to user density, while mmWave shifts to phase noise and intra-cell interference in dense deployments (Rebato et al., 2016). In conclusion, dynamic noise mitigation through beamforming improves the spectral efficiency and reliability of 5G rollout in Indonesia.